Analysis of piezoresistive behavior of polyaniline-coated nylon Lycra fabrics for elbow angle measurement. Issue 2 (1st February 2017) - Muthukumar, N.; Thilagavathi, G.; Kannaian, T.
Abstract: In this article, a textile-based strain sensor has been developed by in situ polymerization of aniline on nylon Lycra fabric. The tensile and repeatability characteristics of the nylon Lycra fabric were studied in Zwick/Roell Z010 tester to analyze the suitability of the fabric for sensor development. After polyaniline coating, the control and coated fabrics have been characterized by means of scanning electron microscopy and energy dispersive X-ray. The change in electrical resistance for the applied strain was studied to analyze the strain sensing behavior of the polyaniline-coated nylon Lycra fabric. From tensile and repeatability study, it was observed that the conditioning cycles are necessary for the nylon Lycra fabric before taking actual measurements in order to improve the stability of the sensor response. The developed fabric had the electrical resistance of 3.5 KΩ/square. The electrical resistance of the developed PANI-coated fabric decreases as the sample is strained and increases again as the strain is relaxed. The measurement of the conductivity change with strain shows that the developed fabric exhibits high strain sensitivity. When used in conjunction with a commercial goniometer, the polyaniline-coated nylon Lycra fabric responded well to the magnitude of bending deformations, demonstrating potential for remote the strain sensing applications.